2022
DOI: 10.1042/bcj20210602
|View full text |Cite
|
Sign up to set email alerts
|

Programmed cell death: the pathways to severe COVID-19?

Abstract: Two years after the emergence of SARS-CoV-2, our understanding of COVID-19 disease pathogenesis is still incomplete. Despite unprecedented global collaborative scientific efforts and rapid vaccine development, an uneven vaccine roll-out and the emergence of novel variants of concern such as omicron underscore the critical importance of identifying the mechanisms that contribute to this disease. Overt inflammation and cell death have been proposed to be central drivers of severe pathology in COVID-19 patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 193 publications
1
38
0
Order By: Relevance
“…Other studies also showed increased expression of genes associated with inflammation in macrophages challenged with SARS-CoV-2 (Abdelmoaty et al 2021) and associated with the caspase pathway and apoptosis (Cardinez et al 2018). It is reported that the inflammasome (NLRP3, associated with IL-18 activation) is activated during SARS-CoV-2 infection, being proposed as an indicator of COVID-19 disease severity, predicting the release of pro-inflammatory cytokines that lead to dysregulated immune responses and tissue damage (Bader et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also showed increased expression of genes associated with inflammation in macrophages challenged with SARS-CoV-2 (Abdelmoaty et al 2021) and associated with the caspase pathway and apoptosis (Cardinez et al 2018). It is reported that the inflammasome (NLRP3, associated with IL-18 activation) is activated during SARS-CoV-2 infection, being proposed as an indicator of COVID-19 disease severity, predicting the release of pro-inflammatory cytokines that lead to dysregulated immune responses and tissue damage (Bader et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The replication of coronaviruses in cells is regulated by many host factors, which can induce drastic structural and physiological changes in cells ( 2 ). During infection, SARS-CoV-2 could induce diverse cell death pathways ( 31 , 32 ), such as apoptosis, necroptosis, pyroptosis, and NETosis in the host cells ( Figure 1B ).…”
Section: Multiple Cell Death Pathways Were Induced In Sars-cov-2 Infe...mentioning
confidence: 99%
“…Coronaviruses (CoVs) were first identified at the beginning of 1900 in domestic animals, and their importance rose since 2003 when three severe CoV human diseases emerged: the Severe Acute Respiratory Syndrome (SARS), the Middle East Respiratory Syndrome (MERS) and the SARS-CoV-2 Infection Disease-19 (COVID-19) [ 168 , 169 , 170 ]. COVID-19 symptoms are similar to SARS, including fever, pneumonia, cough, and in severe cases, serious dyspnea and lung infiltration [ 171 ]. The high infectivity of SARS-CoV-2, the pathogen responsible for COVID-19, caused a rapid spread worldwide and over five million deaths in two years after the disease onset.…”
Section: Rnases and Rna Processing As Tumor And Viral Infection Manag...mentioning
confidence: 99%
“…The high infectivity of SARS-CoV-2, the pathogen responsible for COVID-19, caused a rapid spread worldwide and over five million deaths in two years after the disease onset. Despite the fast vaccine development achievement [ 172 ], as well as the recent approvals of virus-directed therapeutics, this pandemic is far from reaching eradication [ 171 ]. In June 2020, the Orgenesis and Leidos Company started a clinical trial with ONC in COVID-19 infections, after U.S. FDA marketing approval ( .…”
Section: Rnases and Rna Processing As Tumor And Viral Infection Manag...mentioning
confidence: 99%